The Power of a Medical Record Certificate from a Doctor as Evidence of Domestic Violence (KDRT) in Divorce Cases: A Perspective on Legal Considerations of Court Decisions - Agung Hermansyah; Handar Subhandi Bakhtiar; Slamet Tri Wahyudi (Catalist Indo Publisher, 2026)
This study examines the legal position and evidentiary strength of medical record certificates as proof of domestic violence (KDRT) in divorce cases within the Indonesian legal system. Divorce in Indonesia must be based on valid and provable reasons, including domestic violence, which presents complex evidentiary challenges, especially when visum et repertum is unavailable. This research employs a normative legal method using statutory, case, and conceptual approaches, supported by secondary data from legislation, court decisions, and legal literature. The findings indicate that medical record certificates are juridically recognized as written evidence within civil procedural law. However, their evidentiary value is not absolute but categorized as free evidence (vrij bewijs), meaning their strength depends on judicial assessment. Unlike visum et repertum, medical records are not specifically created for legal purposes, which limits their probative value. In judicial practice, judges tend to treat medical records as supporting or circumstantial evidence that must be corroborated by other forms of proof, such as witness testimony or party statements. Court decisions demonstrate that judges prioritize the relevance, consistency, and causal relationship between medical findings and alleged acts of violence. Therefore, medical records cannot stand alone as decisive evidence but play an important role in strengthening the overall evidentiary framework. This study highlights the need for careful judicial consideration and greater clarity regarding the use of medical documents in proving domestic violence in divorce proceedings.